Sampling points with presence of Spintherophyta aurichalcea [Conjunto de datos] - Schapovaloff, Maria Elena; Scherf, Abel Nicolás; Costa, Marcos Ruben; Gramajo, María; Ohashi, Diana Virginia; Ayala, Daniela Sofía (2024)
Ilex paraguariensis (St. Hil.) is a native plant to South America and cultivated in Brazil, Paraguay and Argentina. Spintherophyta aurichalcea (Germar) is reported for the first time damaging yerba mate crops (Ilex paraguariensis St. Hil.) in the provinces of Misiones and Corrientes, Argentina